1998
DOI: 10.1093/rheumatology/37.8.854
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of disease activity in rheumatoid arthritis using magnetic resonance imaging: quantification of pannus volume in the hands

Abstract: We attempted to assess whether pannus volume measured by magnetic resonance imaging (MRI) can be used as an indicator of disease activity in rheumatoid arthritis (RA). Eleven women (mean age 46 yr) with uncontrolled RA were studied for 1 yr. Pannus formation in both hands was quantified using MRI at the start of the study, and at 6 and 12 months thereafter. The volume of enhancing pannus (VEP) was compared with changes in the radiological scores, grip strength, joint tenderness counts, joint swelling counts, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 2 publications
0
13
0
3
Order By: Relevance
“…Qualitative assessments of MRI findings were performed in wrist, MCP, PIP and DIP joints, whereas the quantitative assessment of the synovial membrane volume was only performed in the MCP, PIP and IP joints, because the manual segmentation method is very time-consuming. These joints may be the best markers of disease activity [22] and the total pannus volume of the wrist and finger joints might be more representative for the general outcome of the patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative assessments of MRI findings were performed in wrist, MCP, PIP and DIP joints, whereas the quantitative assessment of the synovial membrane volume was only performed in the MCP, PIP and IP joints, because the manual segmentation method is very time-consuming. These joints may be the best markers of disease activity [22] and the total pannus volume of the wrist and finger joints might be more representative for the general outcome of the patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…The software was calibrated so that it did not calculate values of ME for those voxels in which the initial rate of enhancement was large and consistent with the voxels corresponding to blood vessels such as the digital arteries. Regions of artifactual skin enhancement at the skin–air interface, as previously described (40), were also excluded from calculations.…”
Section: Methodsmentioning
confidence: 99%
“…16 22 23 In these studies all the patients met the American College of Rheumatology (ACR) criteria for RA and had had a long disease duration at entry; in one study median duration was 122 months22 and in another it was five years on average15; a third study focused on joints in which erosive changes on plain films had been found at entry to the study 16. All these studies mainly described changes in the synovium and compared these findings with radiological findings.…”
mentioning
confidence: 99%